2019
DOI: 10.1097/aud.0000000000000754
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Musical Training and Working Memory in Adverse Listening Situations

Abstract: Objectives: Speech-in-noise (SIN) perception is essential for everyday communication. In most communication situations, the listener requires the ability to process simultaneous complex auditory signals to understand the target speech or target sound. As the listening situation becomes more difficult, the ability to distinguish between speech and noise becomes dependent on recruiting additional cognitive resources, such as working memory (WM). Previous studies have explored correlations between WM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 68 publications
1
25
1
Order By: Relevance
“…Similar results transfer to non-speech sounds (Fuller et al, 2014;Başkent et al, 2018). Still, not all studies report a positive effect, and some fail to find a musician advantage even on identical SIN tasks (e.g., QuickSIN and HINT) (Ruggles et al, 2014;Boebinger et al, 2015;Madsen et al, 2017;Yeend et al, 2017;Escobar et al, 2020). The failure to replicate could be due to the small nature of this effect and/or, as we have previously suggested, unmeasured differences in music aptitude even among self-reported musicians that confer perceptual gains in SIN processing (Bidelman and Mankel, 2019).…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…Similar results transfer to non-speech sounds (Fuller et al, 2014;Başkent et al, 2018). Still, not all studies report a positive effect, and some fail to find a musician advantage even on identical SIN tasks (e.g., QuickSIN and HINT) (Ruggles et al, 2014;Boebinger et al, 2015;Madsen et al, 2017;Yeend et al, 2017;Escobar et al, 2020). The failure to replicate could be due to the small nature of this effect and/or, as we have previously suggested, unmeasured differences in music aptitude even among self-reported musicians that confer perceptual gains in SIN processing (Bidelman and Mankel, 2019).…”
Section: Introductionsupporting
confidence: 51%
“…The association between musical training and SIN processing survived after controlling for WM for the QuickSIN (r partial = −0.38, p = 0.045) but not speech streaming (r partial = −0.34, p = 0.08) (cf. Yoo and Bidelman, 2019;Escobar et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, consideration of cognitive training programs such as WM training to improve children's listening ability in noise does not gather support based on the results of this study and other studies (Beaman, 2004;Elliott & Cowan, 2005). Emerging studies in adults are mixed on the outcomes of WM training to improve speechperception-in-noise performance (e.g., Escobar, Mussoi, & Silberer, 2019;Ingvalson, Dhar, Wong, & Liu, 2015;Wayne, Hamilton, Huyck, & Johnsrude, 2016). To our knowledge, while there are several studies in children on WM training, none have been implemented with listening-in-noise ability as an outcome.…”
Section: Discussionmentioning
confidence: 68%
“…[23][24][25] Parbery-Clark et al (2009), evaluated the QuickSIN scores of musicians and nonmusicians and showed that working memory affected the scores, and musicians' results were significantly better in the SIN (Speech in Noise) and QuickSIN tests. 26 On the other hand, Escobar et al (2020), evaluated speech understanding in noise and auditory memory in musicians and non-musicians. They stated no significant difference in musicians' listening efforts and working memory capacities than those not.…”
Section: Discussionmentioning
confidence: 99%